A new method for automated reconstruction of pre-transformation microstructures. (3rd May 2016) - Hadke, Shreyash; Parihar, Manendra Singh; Shekhawat, Satish; Khatirkar, Rajesh Kisni
Abstract: A new method, referred to as the cluster method, is proposed and tested for the reconstruction of pre-transformation microstructure in Ti–6Al–4V alloy. The cluster method begins by constructing clusters of daughter grains (room-temperature hcp α -phase) that have a high probability of being transformed from the same parent grain (high-temperature bcc β -phase). These clusters are then grown, and back-transformed to the parent grain orientations using the 'summation of mutual misorientation angle method' (SMMA method). The cluster method is validated by comparing the obtained results with the results of the SMMA and triplet methods.